Content and structural components of technology of formation of culture of intellectual work. (Journal of Educational Sciences, 2017)
In this article theoretical provisions and conclusions are the scientific basis for the development and implementation of new models and technologies of professional and creative development specialists. Content and structural components of technology are the basis for creative adaptation and enrichment of the person skilled in the relevant methods, techniques and techniques with the introduction of multi-level training of bachelor –master, the new education standards. Content and structural components of the technology allows to design various types of educational, creative, cognitive activity, contributing to the formation of a productive professional and competent activity of future specialists.